The role of frailty in the relationships between social relationships and health outcomes: a longitudinal study - Fereshteh Mehrabi; François Béland (BMC, 2024)
Abstract Background Socially isolated older adults incur increased risks of adverse health outcomes, though the strength of this association is unclear. We examined whether changes in physical frailty moderated the associations between changes in social relationships and changes in health outcomes among older adults. Methods This longitudinal study is based on three waves of the FRéLE study among 1643 Canadian community-dwelling older adults aged 65 years and older over 2 years. We performed latent growth curve modelling (LGMs) to assess changes with the assumption of missing not at random, adjusting for time-invariant covariates. We used the latent moderated structural equations (LMS) to test the interactions in LGMs. Social relationships were measured by social participation, social networks, and social support from different social ties. Frailty was assessed using the five components of the phenotype of frailty. Results The results revealed that changes in frailty moderated changes in social participation (β = 3.229, 95% CI: 2.212, 4.245), social contact with friends (β = 4.980, 95% CI: 3.285, 6.675), and social support from friends (β = 2.406, 95% CI: 1.894, 2.917), children (β = 2.957, 95% CI: 1.932, 3.982), partner (β = 4.170, 95% CI: 3.036, 5.305) and extended family (β = 6.619, 95% CI: 2.309, 10.923) with changes in cognitive function and depressive symptoms, but not with chronic diseases. These results highlight the beneficial role of social relationships in declining depressive symptoms and improving cognitive health among older adults experiencing increases in frailty. Conclusions The findings suggest that changes in social support have a protective and compensatory role in decreasing depressive symptoms and enhancing cognitive health among older adults with increasing frailty. Public health policy and strategies should consider the impact of social support on multiple health outcomes among older adults with increasing frailty. Further experimental studies and interventions are warranted to extend findings on the relationships between social relationships and health outcomes, targeting frail older adults. Future studies may also consider other health-related risk factors that may impact the associations between social relationships and health outcomes among older adults.